PENGARUH PEMBERIAN OXYTOCIN DAN EKSTRAK PEPAYA TERHADAP KADAR HORMON PROLAKTIN DAN VOLUME ASI PADA NORMAL PASCA PARTUM IBU - Afriannisyah, Entan; Poppy Siska Putri; Juanda Syafitasari (Program Studi D III Kebidanan Akademi Kesehatan Sapta Bakti Bengkulu, 2024)
WHO targets exclusive breastfeeding of 70% by 2030, in 2015-2021 already 48% of babies under 6 months are exclusively breastfed and almost approaching the target set by the World Health Assembly (WHA), namely 50% in 2024. Pain and the stress experienced by the mother will cause the blood vessels to narrow so that the distribution of the hormones prolactin and oxytocin from the brain to the breasts will be delayed. Breast milk is the best food for babies and has many benefits for babies and mothers cannot. provided optimally. To stimulate the hormone prolactin, you can also do oxytocin massage because it can stimulate endorphin hormones which have the effect of reducing stress and reducing pain, causing vasodilation of blood vessels so that the hormone prolactin can be produced without inhibitors. The hormones prolactin and oxytocin play a role in increasing breast milk production. Prolactin plays a role in the synthesis of breast milk, while oxytocin activity in the mammary glands causes contraction of myoepithelial cells, so that breast milk is pushed into the milk ducts. The aim of this study was to analyze prolactin levels and breast milk volume in postpartum mothers through oxytocin massage and papaya extract. Methods: A literature review was conducted using direct science electronic databases. google sholar. The effect of oxytocin and papaya extract on prolactin hormone levels and breast milk volume were used as keywords in the search strategy, publications from 2009 to 2019. Results: Several studies show that oxytocin and papaya extract massage in breastfeeding mothers can stimulate and increase the secretion and amount of milk production (ASI). Conclusion: Oxytocin massage and administration of papaya extract in the form of leaves, ripe papaya fruit and young papaya are effective in increasing prolactin hormone levels and breast milk volume in normal postpartum mothers, and papaya extract is safe for consumption by postpartum (breastfeeding) mothers.